PREFERENSI WISATAWAN BERPASANGAN MANCANEGARA TERHADAP PRODUK WISATA DI GILI TRAWANGAN, LOMBOK UTARA, NUSA TENGGARA BARAT - Zyendira Amanda Zanuar; I Made Sendra; I GPB. Sasrawan Mananda (Department of Tour and Travel Studies, Faculty of Tourism, Udayana University, 2017)
This study discusses on couple tourist preferences of the tourism product in Gili Trawangan, including it’s characteristics. Preferences is a choice on alternatives based on their relatives utility, a process which results in an optimal choice (whether real or theoretical). The aim of this study is to determine how couple tourist preference of the tourism product in Gili Trawangan. Methods of data collection utilized observation, questionnaire, literature study, and documentation. The result show that the characteristic of the couple tourist in Gili Trawangan are divided into tourist descriptor and trip-descriptor. The characteristic of tourist descriptor is dominated by couple tourists from Europe, whose age are 25-44 years with the single status and the young couple. Moreover, the characteristic of a trip-descriptor is dominated by couple tourists. The purpose of their traveling to Gili Trawangan is the holiday. Most of them received information from the internet who arranged their own travel and they traveled during the holiday season with the length of stay is 2-3 days in Gili Trawangan. As for couple tourist preferences to Gili Trawangan divided into 4 preferences, i.e the preference based on transportation, accommodation, the place to have a meal, and tourist activity. In term of transportation the couple tourist preferred bicycle and in term of accommodation they preferred homestay. Concerning the place having a meal they preferred to a restaurant and for as tourism activity they preferred snorkeling.